SISTEM INFORMASI PERSEDIAAN OBAT PADA PUSKESMAS BATUARA BERBASIS WEBSITE - Arena, Tina; Farida, Farida; Perawati, Perawati (journal Informatika, Multimedia, dan Informasi, 2025)
This study aims to: 1) facilitate the warehouse in batuara Health Center drug supplies 2) determine the response of users to The Information System Prsediaan drugs in Batuara Health Center-based Website. This study uses the Waterfall research method is a software development model in order. Waterfall research method has several stages, namely: analysis stage, design stage, coding stage, testing stage and maintenance stage (maintenance). The results of this study showed that 1) drug inventory information system is designed using PHP programming language MySQL Database and UML (Unified Model Language) design language, namely Usecase Diagram, Activity Diagram, Sequence Diagram and Class Diagram. 2) to determine the response of drug inventory Information System users using the system usability scale (SUS) by knowing the score obtained with the results of 82% of 10 respondents with the value of the letter A and the category is very good.